2018
DOI: 10.1016/j.ejon.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to delivering advanced cancer nursing: A workload analysis of specialist nurse practice linked to the English National Lung Cancer Audit

Abstract: Purpose: Health services across the world utilise advanced practice in cancer care. In the UK, lung cancer nurse specialists (LCNS) are recognised as key components of quality care in national guidelines, yet access to LCNS contact is unequal and some responsibilities are reportedly left undone. We assess whether any variation in working practices of LCNS is attributable to factors of the lung cancer service at the hospital trust. Method: Nationwide workload analysis of LCNS working practices in England, linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
10
0
3
Order By: Relevance
“…However, patients' compliance with yoga breathing training is an important prerequisite to affect its effect. Some researchers have reported that patients' compliance with postoperative rehabilitation training is poor, and some reasons affecting compliance include the traditional belief that patients should stay in bed after surgery, and traditional health education is mainly based on individual knowledge indoctrination which cannot change the attitude and behavior of patients [ 20 ]. In addition, some patients can understand the importance of rehabilitation training, but they will encounter some problems that will reduce compliance during the training process, such as fear of wound pain, physical fatigue, depression, lack of supervision by medical staff, and lack of social support.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients' compliance with yoga breathing training is an important prerequisite to affect its effect. Some researchers have reported that patients' compliance with postoperative rehabilitation training is poor, and some reasons affecting compliance include the traditional belief that patients should stay in bed after surgery, and traditional health education is mainly based on individual knowledge indoctrination which cannot change the attitude and behavior of patients [ 20 ]. In addition, some patients can understand the importance of rehabilitation training, but they will encounter some problems that will reduce compliance during the training process, such as fear of wound pain, physical fatigue, depression, lack of supervision by medical staff, and lack of social support.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of 15,967 people with a primary lung cancer diagnosis over five survey waves demonstrated that more advanced staging is not always associated with lower satisfaction, which may reflect distress regarding pathway or prognostic uncertainties in early stage lung cancer. Positive experiences at later stage diagnoses were most apparent in the dimension of clinical staff support and when stratified by those who received surgery, supporting the role of advanced practice nursing in addressing holistic needs in limited disease [ 20 ]. In the small sample of people diagnosed through the elective inpatient route, people were more likely to report more positive experiences compared to GP referral, particularly within treatment modalities that included radiotherapy, which is in contrast to people with colorectal cancer for whom NHS screening is available [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previously validated self‐completed questionnaire was utilised to gain responses from a variety of roles in primary and community care (Leary, Mason, & Punshon, 2018; Stewart et al, 2018). The workload questionnaire was based on a previous evaluation of the work left undone in oncology nursing (Leary, White, & Yarnell, 2013).…”
Section: Methodsmentioning
confidence: 99%